Dietary sesame diminishes bone mass and bone formation indices in ovariectomized rats - R. Tachibana; H. Matsushita; A. Minami; N. Morita; S. Shimizu; H. Kanazawa; T. Suzuki; K. Watanabe; A. Wakatsuki (IMR Press, 2020)
Purpose: This animal experiment investigated how sesame seed (Sesamum indicum; SSI) extract affects bone metabolism in ovariectomized (Ovx) rats. Materials and methods: Female Wistar rats (12 weeks old) were randomly assigned to the Baseline control (BC), Sham, Ovx, and Ovx + SSI groups (n = 6-10). Animals in the BC group were sacrificed immediately. Rats in the other groups underwent sham surgery (Sham) or bilateral ovariectomy (Ovx and Ovx + SSI). Rats in the Ovx + SSI group were given custom diets, and BMD and bone histomorphometry were evaluated 13 weeks post-surgery. Results: The femur BMD in the Ovx + SSI group was lower than in the Ovx group, as were the measurements for bone formation rate and mineralizing surface. Conclusion: Administration of a methanol extract of sesame seeds decreased femur BMD in Ovx rats.